2022
DOI: 10.1111/ajo.13560
|View full text |Cite
|
Sign up to set email alerts
|

Primary dysmenorrhoea in adolescents and young women: A twin family study of maternal transmission, genetic influence and associations

Abstract: The extent to which maternal transmission of primary dysmenorrhoea is genetically determined in adolescents and young women has yet to be determined. We aimed to assess heritability and associations relevant to primary pain syndromes using a twin family study. Methods:Participants were young menstruating female twins, and their oldest sisters and mothers, whose families were registered with Twins Research Australia and previously participated in a twin family study of primary paediatric pain disorders. Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…There is also the consideration that life prevalence (>3 months) of doctor-confirmed iron deficiency, notably including iron deficiency identified in the first year of life, be considered as an association, probably causal as suggested by application of the Bradford Hill criteria, with dysmenorrhea, and thus a biological influence. 1 There was an association between the history of iron deficiency and pain intensity of the current menstrual period after adjustment for age (OR 1.60, P < 0.01) 1 . The association between a history of doctor-confirmed iron deficiency and dysmenorrhea has been confirmed in adult women in a current twin family study.…”
Section: Letter To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…There is also the consideration that life prevalence (>3 months) of doctor-confirmed iron deficiency, notably including iron deficiency identified in the first year of life, be considered as an association, probably causal as suggested by application of the Bradford Hill criteria, with dysmenorrhea, and thus a biological influence. 1 There was an association between the history of iron deficiency and pain intensity of the current menstrual period after adjustment for age (OR 1.60, P < 0.01) 1 . The association between a history of doctor-confirmed iron deficiency and dysmenorrhea has been confirmed in adult women in a current twin family study.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Whether this is due to genetic or social learning factors is unknown.” I suggest that both are important. I was a co-author of a twin family study on dysmenorrhea in adolescents and young women, 1 published almost simultaneously with the review by Gagnon et al, and this publication would not have been apparent to the authors. After reviewing maternal transmission of dysmenorrhea, we presented evidence from a questionnaire survey of 103 twin pairs and their families for substantial genetic influence.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Aouad et al recently performed a twin study for primary dysmenorrhea, where monozygotic twins showed twice the correlation for different pain phenotypes compared to dizygotic twins, with heritability estimates between 57% and 67%. 21 A genome-wide association study https://doi.org/10.2147/IJWH.S380006…”
Section: Pathophysiologymentioning
confidence: 99%
“…4,5 This would help explain the observed association between iron deficiency and period pain discussed in Dr. Champion's letter. Given the cross-sectional nature of the data, causality between dysmenorrhea and iron deficiency cannot be determined by the investigation of Aouad et al 1…”
Section: Letter To the Editormentioning
confidence: 99%